2003
DOI: 10.1002/chem.200390211
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the Elucidation of the Pseudopericyclic Character of the Cyclization of (Z)‐1,2,4,6‐Heptatetraene and Its Heterosubstituted Analogues: Magnetic Properties and Natural Bond Orbital Analysis

Abstract: The electrocyclization of heterosubstituted derivatives of (Z)-1,2,4,6-heptatetraene, (2Z)-2,4,5-hexatrien-1-imine and (2Z)-2,4,5-hexatrienal exhibit some features which suggest a pseudopericyclic mechanism. In order to examine this, a comprehensive study including the determination of magnetic properties to estimate aromaticity and an NBO analysis throughout the reaction path was conducted. The cyclization of 5oxo-2,4-pentadienal, a process of unequivocal pseudopericyclic nature, was studied for comparison. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
93
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 48 publications
11
93
2
Order By: Relevance
“…Electrocyclic ring opening (ERO) of pyrone has been found to be pseudeopericyclic by Birney and coworkers 27 and later Rodríguez and coworkers 28 have confirmed this by using NBO analysis. We [29][30] have studied the thermolysis of 2-pyrone and 6-halo-2-pyrone and have found that fluorine substitution substantially altered the potential energy surface for ERO, sigmatropic rearrangement and electrocyclic ring closing (ERC) of pyrones.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Electrocyclic ring opening (ERO) of pyrone has been found to be pseudeopericyclic by Birney and coworkers 27 and later Rodríguez and coworkers 28 have confirmed this by using NBO analysis. We [29][30] have studied the thermolysis of 2-pyrone and 6-halo-2-pyrone and have found that fluorine substitution substantially altered the potential energy surface for ERO, sigmatropic rearrangement and electrocyclic ring closing (ERC) of pyrones.…”
Section: Introductionmentioning
confidence: 80%
“…This is in agreement with proposition that the involvement of LP of hetero atom may push the pericyclic reaction to become more pseudopericyclic. 28 …”
Section: Bond Critical Property Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…In previous papers we have demonstrated the necessity to study the whole process and not only the transition state in order to define a process conclusively as pericyclic or pseudopericyclic. [2][3][4][5] In addition, we have emphasised the importance of studying the magnetic properties along the reaction profile in this controversial matter. [5] Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, this work reports a comprehensive study of the magnetic properties along the reaction profile of the whole cyclisation of 3-azidopropenal. [2][3][4] The aromaticity was examined in terms of magnetic susceptibility (χ), magnetic susceptibility anisotropy (χ anis ) and the nucleus-independent chemical shifts (NICS) reported by Schleyer. [25] Birney [15] found that disconnections can also occur in coarctate reactions, similarly to pseudopericyclic reactions.…”
Section: Introductionmentioning
confidence: 99%